Composition Changes in Lycium ruthenicum Fruit Dried by Different Methods - Lu, Youyuan; Kong, Xiangfeng; Zhang, Juanhong; Guo, Chao; Qu, Zhuo; Jin, Ling; Wang, Hanqing (Frontiers in Nutrition, 2021)
The fruit of Lycium ruthenicum (LRF), known as black wolfberry, is a medicinal and edible fruit. The fresh LRF is perishable, and only about 3 days for the shelf life. Drying could prolong the shelf life of LRF. However, it could imply physical changes and chemical modification. This study evaluated the effect of sun drying (SD), hot air drying (HD) and freeze drying (FD) on the appearance characteristic, moisture content, bioactive compounds, amino acid composition and antioxidant activity of LRF. The results showed that LRF dried by FD was round, expansion, fragile, and maintained the largest amount of appearance traits among the three drying methods. Drying methods had a significant effect on phytochemicals content and antioxidant activity of LRF (P<0.05). Principal component analysis showed that procyanidin content (PAC), asparagine (Asn), total phenolic content (TPC), total anthocyanin content (TAC) and moisture content were the main sources of the difference in LRF dried by different methods. The characteristic of LRF in FD was low moisture content, and high TPC, Asn, PAC and TAC. SD was opposite to FD. HD was high TPC and low TAC content. The quality of LRF was in the order of FD > HD > SD based on comprehensive evaluated the phytochemical component content and antioxidant capacity. Additionally, the water temperature and soaking time had different antioxidant activity effect on LRF dried by different methods. These findings will provide useful information for production and utilization of LRF.